Sex differences in the development of experimental diabetic retinopathy - Chen, Ying; Schlotterer, Andrea; Lin, Jihong; Dietrich, Nadine; Fleming, Thomas; Lanzinger, Stefanie; Holl, Reinhard W.; Hammes, Hans-Peter (Scientific reports, 2024)
This study aimed to characterize the role of female sex in the pathogenesis of diabetic retinopathy. In the retinae of female Ins2Akita-diabetic mice (F-IA), ovariectomized female Ins2Akita-diabetic mice (F-IA/OVX), male Ins2Akita-diabetic mice (M-IA), and female STZ-diabetic mice (F-STZ), the formation of reactive metabolites and post-translational modifications, damage to the neurovascular unit, and expression of cellular stress response genes were analyzed. Compared to the male diabetic retina, the concentrations of the glycation adduct fructosyl-lysine, the Maillard product 3-deoxyglucosone, and the reactive metabolite methylglyoxal were significantly reduced in females. In females, there was also less evidence of diabetic damage to the neurovascular unit, as shown by decreased pericyte loss and reduced microglial activation. In the male diabetic retina, the expression of several members of the crystallin gene family (Cryab, Cryaa, Crybb2, Crybb1, and Cryba4) was increased. Clinical data from type 1 diabetic females showed that premenopausal women had a significantly lower prevalence of diabetic retinopathy compared to postmenopausal women stratified for disease duration and glycemic control. These data emphasize the importance of estradiol in protecting the diabetic retina and highlight the pathogenic relevance of sex in diabetic retinopathy.
Gesehen am 14.05.2025